Thermal oxidation and nitridation of sputtered Zr thin film on Si via N2O gas - Wong, Y.H.; Cheong, K.Y. (Elsevier, 2011)
Formation of ZrO2 by simultaneous thermal oxidation and nitridation in nitrous oxide of sputtered Zr on Si substrate is reported here for the first time. Sputtered Zr on Si substrate and followed by oxidation and nitridation in nitrous oxide ambient at 700 °C for various durations (5–20 min) have been systematically investigated. The structural and chemical properties of the samples were examined. Chemical depth profiles of the samples have been evaluated by X-ray photoelectron spectroscopy. Stoichiometric Zr–O (ZrO2) and its interfacial layer consisted of mixed sub-stoichiometric Zr–O, Zr–N, Zr–Si–O, Si–N, and/or Si–O–N phases were identified. A possible model related to the oxidation and nitridation mechanisms has been proposed and explained. Supportive results related to the model were obtained by energy filtered transmission electron microscopy, X-ray diffraction, Raman spectroscopy and Fourier Transform infrared analysis.